Traceability in analytical atomic spectrometry: elemental analysis comes full circle. Issue 11 (11th September 2020) - Sargent, Mike
Abstract : Recent development of a global infrastructure for chemical measurements allows laboratories using atomic spectrometry to easily and efficiently report traceable measurement results. Abstract : For thousands of years the need for measurements which are comparable at different locations and at different moments in time has been met using the concept of traceability. The way in which this concept functions, and its limitations, are described together with the international effort since the 19 th century to underpin traceable physical measurement values with a global infrastructure. It is shown how the physical measurement infrastructure also served to underpin traceable elemental analysis results whilst they were obtained by classical analysis methods. The almost universal replacement of these methods by atomic spectrometry introduced a need for chemical calibration standards and matrix reference materials with traceable values. However, no comparable chemical measurement infrastructure existed and for a time the benefits of traceable results in elemental analysis were largely forgotten. The extension of the international measurement infrastructure to chemical measurements is described, emphasising the formation of the Consultative Committee for Metrology in Chemistry (CCQM) and the activities of its Inorganic Analysis Working Group (IAWG). As a result, any laboratory using atomic spectrometry in accordance with current best practice should be able to provide traceable measurement results. Traceability of elemental analysis results has indeed come full circle, although atomic spectrometry facilitates more than elemental analysis and work remains to be done with some other applications.